Effectiveness of low-level gallium aluminium arsenide laser therapy for temporomandibular disorder with myofascial pain: A systemic review and meta-analysis. Issue 52 (30th December 2021) - Wu, Xuelian; Zhu, Jiang; Zheng, Bing; Liu, Jie; Wu, Zonghui
Abstract : Supplemental Digital Content is available in the text Abstract: Purpose: Temporomandibular disorder (TMD) causes masticatory muscle pain and mouth opening limitations and affects patients' ability to eat, practice oral health and perform other activities of daily living. Although the benefits of low-energy lasers in treating TMD have been reported, the results vary greatly depending on the equipment used and the energy output. This study systematically evaluated the efficacy of a low-level gallium aluminium arsenide (GaAlAs) laser treatment for TMD with myofascial pain and maxillary pain. Methods: We searched the PubMed, EMBASE, Cochrane Library, Web of Science, and ClinicalTrials.gov databases for randomized controlled trials (RCTs) published since database inception to April 5, 2020, that compared low-level laser treatment to sham/placebo treatment or no intervention in patients suffering from TMD with myofascial pain. Three reviewers independently screened the literature, extracted data, and assessed the quality of the included studies according to the risk-of-bias tool recommended by the Cochrane Handbook V.5.1.0 (Cochrane Collaboration, London, UK). Then, a meta-analysis was performed using RevMan 5.3 and Stata 15.1 software. Results: The data from 8 randomized controlled trials including 181 patients were analyzed. The severity of myofascial TMD pain (measured on a visual analogue scale, VAS) at the end of treatment was significantly different between the control laser therapy and the low-level GaAlAs laser therapy (weighted mean difference [WMD] = −0.76, 95% confidence interval [CI] −1.51 to 0.01, P = .046); at 3 to 4 weeks after treatment, there was no significant difference (WMD = 1.24, 95% CI −0.04 to 2.51, P = .057). In addition, there was no significant improvement in maximum mouth opening (MMO) at the end of treatment (WMD = −0.03, 95% CI −4.13 to 4.06, P = .987) or at 3 to 4 weeks after treatment (WMD = 1.22, 95% CI −2.94 to 5.39, P = .565). Conclusions: The results of this study suggest that there is insufficient evidence to indicate an efficacy of low-level GaAlAs laser therapy in improving TMD pain and maximal oral opening. These results suggest that clinicians should make appropriate recommendations to inform patient decision-making.